Preparation of Mesoporous Si@PAN Electrodes for Li-Ion Batteries via the In-Situ Polymerization of PAN. (1st January 2015) - Yersak, Thomas A.; Shin, JaeWook; Wang, Ziying; Estrada, Daniel; Whiteley, Justin; Lee, Se-Hee; Sailor, Michael J.; Meng, Ying Shirley
Abstract : This paper details a new binder for mesoporous Si (mp-Si) via the in-situ polymerization and stabilization of polyacrylonitrile (PAN). Using this method mp-Si@PAN electrodes for Li-ion battery anodes have been fabricated. Though the mp-Si@PAN electrodes delivered a reversible specific capacity in excess of 800 mAh g −1 (electrode), the first cycle coulombic efficiency of these electrodes was still less than 50% without a pre-lithiation treatment. The results of an all-solid-state battery experiment confirmed that low first cycle reversibility should be attributed primarily to mechanical pulverization of the internal porous structure of mp-Si particles.